2016
DOI: 10.18632/oncotarget.13518
|View full text |Cite
|
Sign up to set email alerts
|

Gremlin promotes retinal pigmentation epithelial (RPE) cell proliferation, migration and VEGF production via activating VEGFR2-Akt-mTORC2 signaling

Abstract: Retinopathy of prematurity (ROP) is characterized by late-phase pathologic retinal vasoproliferation. Gremlin is a novel vascular endothelial growth factors (VEGF) receptor 2 (VEGFR2) agonist and promotes angiogenic response. We demonstrated that gremlin expression was significantly increased in retinas of ROP model mice, which was correlated with VEGF upregulation. In retinal pigmentation epithelial (RPE) cells, gremlin activated VEGFR2-Akt-mTORC2 (mammalian target of rapamycin complex 2) signaling, and promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…In agreement, staining of the tumor tissue with CD31 antibodies showed more staining and larger vessels in JP5/grem1 tumors (Figure 9B ). Gremlin-1 can signal through the VEGFR2 and it has also been recently linked to the regulation of VEGF expression in pigmentation epithelial cells [ 8 , 18 ]. Notably, VEGFA mRNA expression was decreased in gremlin-1 silenced mesothelioma cells and increased in JP5/grem1 cells as compared to the controls (Figure 9C ).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement, staining of the tumor tissue with CD31 antibodies showed more staining and larger vessels in JP5/grem1 tumors (Figure 9B ). Gremlin-1 can signal through the VEGFR2 and it has also been recently linked to the regulation of VEGF expression in pigmentation epithelial cells [ 8 , 18 ]. Notably, VEGFA mRNA expression was decreased in gremlin-1 silenced mesothelioma cells and increased in JP5/grem1 cells as compared to the controls (Figure 9C ).…”
Section: Resultsmentioning
confidence: 99%
“…Downstream activation of VEGFR2 includes ERK1/2, p38, Src and Akt pathways [8]. Seen in retinal pigment epithelial cells, GREMLIN, via VEGFR2, activates Akt-mTORC2 (mammalian target of rapamycin complex 2) signaling, and promotes cell proliferation, migration and VEGF production [63]. Commented above, PI3K is a key pathway in Nephrin signaling [37].…”
Section: Discussionmentioning
confidence: 99%
“…GREM1 increases hyperplasia and the invasiveness of synoviocytes via activation of ERK and Akt [47]. GREM1 activates the Akt signaling to promote proliferation, migration, and VEGF production in retinal pigmentation epithelial cells [48]. GREM1 utilizes both TGF-β/Smad and JNK/p38 MAPK signaling pathways to induce extracellular membrane proteins in human trabecular meshwork cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that GREM1 can directly bind to VEGFR2 [51]. The GREM1-VEGFR2 pathway is involved in renal inflammation [52] and the proliferation of retinal pigmentation epithelial cells [48]. In addition, GREM1 induces EMT via VEGFR2 activation in tubular epithelial cells [36].…”
Section: Discussionmentioning
confidence: 99%